Northern Adriatic meteorological tsunamis: Assessment of their potential through ocean modeling experiments. Issue 4 (18th April 2015) - Šepić, Jadranka; Vilibić, Ivica; Fine, Isaac
Abstract Potential for generation of meteotsunami waves via open ocean resonance has been documented for the shallow northern Adriatic, based on a set of barotropic numerical modeling experiments. Model simulations were forced by a bell‐shaped traveling atmospheric (air pressure, wind) disturbance, with shape and propagation parameters chosen in accordance with measurements done during several observed northern Adriatic meteotsunamis. Air pressure disturbances were found to generate much larger meteotsunami waves than wind disturbances, with wind disturbances having a limited influence in the very coastal and shallow areas only. Numerical simulations reveal that the most important factor for generation of large meteotsunami waves is matching between the speed of the atmospheric disturbance and the speed of long‐ocean waves. Already a small (∼10%) deviation from resonant conditions stops the wave growth and dramatically decreases height of predicted waves. A train of atmospheric disturbances can significantly increase maximum wave heights at selected locations at which multiple reflections and superimpositions of meteotsunami waves occur. Sensitivity of model simulations to resonant conditions and limited cross‐propagation width of atmospheric disturbance explain the localization of destructive meteotsunami waves in a limited area during destructive historic events. Mapping of maximum predicted wave heights indicates places with large meteotsunami hazard potential, matching the locations where real events were observed, and may be a useful tool for assessing vulnerability and risks in coastal areas during extreme sea level events.